Toward an intelligent high frequency AC distributed power system - Part II: Analytical modelling and experimental realization - Luk, Patrick Chi-Kwong; El-Hasan, T. S. (Praise Worthy Prize, 2016)
High frequency AC (HFAC) distributed power systems (DPS), where electric power is delivered at up to multi-kHz via cables, is an alternative means to conventional centralized power systems. This paper explores the means by which real-time information can be achieved without installing additional physical communication channels on an existing 50 kHz current-fed HFAC DPS in lighting applications. A communication protocol is methodologically developed to facilitate robust and efficient inter-device real-time communication. In addition, analytical modelling for the current fed coupling circuit is presented. The utility of an intelligent HFAC DPS is demonstrated by experimental results from comprehensive circuit level implementation. Copyright © 2016 Praise Worthy Prize - All rights reserved.
Keywords: Modems; Data communication; Intelligent Power Distribution; Energy Management; Power Distribution Systems; High Frequency AC; Lighting Systems